Assessment of indirect cost-of-illness in a subsistence farming society by using different valuation methods - Tin, Tin Su; Sanon, Mamadou; Flessa, Steffen (Elsevier, 2007)
Indirect costs or productive labour time lost are the largest share of household economic burden of illness. However, the estimate of household indirect cost can vary depending on the valuation methods used. We therefore estimated household indirect cost in a subsistence farming society in Burkina Faso based on daily production value. These results were validated by using willingness-to-pay method and current wage rate. Among the three methods, the value of a day lost for adults assessed by willingness-to-pay method was considerably higher than other methods. There were no significant differences in indirect costs estimated by daily production value and wage rate. There were significantly higher indirect costs for households which were of higher economic status when daily production value was used. It might raise a question of equity. The willingness-to-pay method can capture the various aspects of indirect cost such as differences among age groups and gender, important individual characteristics and seasons. Thus, it is an appropriate approach for rural subsistence fanner communities. Estimation of indirect cost by wage rate can also be used as a rapid estimation of indirect cost in a rural area in developing countries as an alternative for daily production value. (c) 2007 Elsevier Ireland Ltd. All rights reserved.